Pemilihan Karier sebagai Akuntan Publik bagi Mahasiswa Universitas Lampung dengan Pendekatan Theory of Planned Behavior - Santi Dwina Dewanti; Fajar Gustiawaty Dewi; Rindu Rika Gamayuni; Komarudin Komarudin (Penerbit Goodwood, 2023)
Purpose: This research aims to see how attitudes, subject norms, behavioral perception control and GPA on the interest in a career as a Public Accountant in the perception of accounting students at the University of Lampung Research methodology: This research is a quantitative research. The data were collected using questionnaire survey. In order to achieve the goal study, this study was conducted by examining 347 respondents. The analysis method in this study used the Bootstrapping Test which is analyzed using the smart PLS 2021 program. Results: The result showed that attitudes and perceived behavioral control did not have a positive effect on the career interest of accounting students as public accountants. Limitations: This research was only conducted at 4 variables, namely attitudes, subjective norms, behavioral perception control, and GPA. This can be ignored by several indicators or other variables that have a greater contribution or reason to interest in a career as a Public Accountant. Contributions: This study has contributions to the enrichment of the theoretical approach of planned behavior, especially the involvement of accounting student behavior perception control as public accountants.